Oxidative stress in erythrocytes of banked ABO blood. Issue 10 (25th November 2016) - Carl, Hsieh; Soumya, Ravikumar; Srinivas, Prabhu; Vani, Rajashekharaiah
Abstract : Objective : To understand the responses of A, B, and O blood groups to oxidative stress (OS) induced through storage. Methods : A, B, and O blood units were obtained from the blood bank at KIMS Hospital, Bangalore, and stored for 35 days at 4°C in citrate phosphate dextrose adenine-1 solution. Every fifth day, hemoglobin (Hb) was assessed in whole blood and erythrocytes were isolated from each group. OS markers such as (i) antioxidant enzymes [superoxide dismutase and catalase] and superoxides were assessed in hemolysate; (ii) lipid peroxidation product – malondialdehyde (MDA) and protein oxidation products [protein carbonyls, advanced oxidation protein products (AOPP), and protein sulfhydryls] were assessed in membrane ghosts. Results : Antioxidant enzymes and Hb were similar in all groups. Superoxides increased in blood group O. MDA and AOPP differed between the groups, where levels in blood group O were lower than blood groups A and B. Sulfhydryls were maintained throughout storage. Discussion : The antioxidant defense in A, B, and O groups were similar as evident from our results of Hb, antioxidant enzymes and sulfhydryls. However, the response of blood group O diverged from that of A and B, substantiated by the results of MDA, AOPP, and superoxides. Thus blood group O endured oxidative insult more efficiently than A and B. This study forms the basis for future studies on erythrocyte membrane and exploring blood group O as a potential candidate for prolonging storage.